EDMONS (Edukasi & Demonstrasi) terhadap Pengetahuan Masyarakat tentang Tas Siaga Bencana Erupsi - Damayanti, Didit; Girianto, Pria Wahyu Romadhon; Kurniati, Widiya (STIKES Ngesti Waluyo, 2023)
Volcanic eruption is a serious problem for Indonesia because Indonesia is located on the Ring of Fire. The lack of disaster knowledge makes people do not know how to prevent the greater impact of disasters. The purpose of the study was to determine the effect of EDMONS (education and demonstrations) on public knowledge about eruption disaster preparedness bags in Sugihwaras Village, Ngancar District, Kediri Regency. The research used a pre-Experimental Design approach of one group pretest-posttest design. The cluster sampling technique was used to obtain 46 respondents of 210 populations. The respondents were heads of families. The instrument used was a disaster preparedness bag knowledge questionnaire, while the statistical test used was Wilcoxon Signed Rank Test with α=0.05. The results of the study were: before the EDMONS intervention were given all (100%) respondents had less knowledge. After being given the intervention, almost all (91.3%) respondents were well informed. The results of the analysis obtained a p-value of 0.000 (≤α 0.05), so because of the p-value is less than α, it means that there is a significant influence of EDMONS on public knowledge about eruption disaster preparedness bags in Sugihwaras Village, Ngancar District, Kediri Regency. The EDMONS method is a combination of very interesting, interactive, and effective methods, so that respondents get more knowledge about eruption disaster preparedness. We recommend that this method can be socialized throughout the community as an eruption disaster preparedness effort.